Pengaruh Kontrasepsi Hormonal Planibu® Versus Depo Progestin® terhadap Fungsi Hepar dan Profil Lipid - Djaswadi Dasuki, Olga Sanger, Flourisa J Sudradjat 3, Enny S Pamuji (Berita Kedokteran Masyarakat (BKM), 2008)
Background:  Injectable  contraception was  used  by  about   15% of  contraceptive  users  in  Indonesia. Safety  of injectable  contraceptive was  necessary  to  study  before  Planibu® was marketed  in  Indonesia. Safety was measured  through  liver  function and  lipid profile  parameters.Objectives: To  compare  safety of Planibu® versus Depo Progestin®  that was measured with  liver  function  and lipid profile  parameters Design of  Study: “Double  Blind Randomized Controlled Trial  (Double  Blind RCT)”  Planibu®  versus Depo Progestin®”  nested  on  longitudinal  surveillance  and  community  based  study  in  Purworejo  district  (LPKGM centre)  and Manado municipality  (Manado  centre)Methods: Study  population was  childbearing age women, married  and wanted  to delay  or  space  pregnancy with  injectable  contraceptive  in Purworejo district  and Manado  municipality. Clinical,  gynecological and  laboratory examination was done  before  injectable  contraceptive was  administered. Laboratory  examination  included  liver function SGOT, SGPT and  lipid profile HDL, LDL  and  total  cholesterol. Eligible Subjects who met  inclusion  and exclusion  criteria were  70 women.   As many as  35 women  received Planibu®  injection and  35 women  received Depo Progestin®  injection every  3 months  for 12 months  in  the same  time. Before  injection was  administered, venous  blood sampling was  taken  from each  subject.Results: Before  using  contraception,  there was  no  statistical  difference  of  liver  function  and  lipid  profile parameters between group Planibu® and Depo Progestin® (p>0,05). There was a statistically significant difference in the level of  cholesterol, HDL, and SGOT  during the 12 month of use Depo Progestin®  (p=0,000, p=0,009 and p=0,000), although  clinically  it wasn’t significantly  different. There was a  statistically significant  difference  in  the level of   cholesterol, SGOT and SGPT during  the 12 month of use   Planibu®  (p =0,038, p=0,000 dan p=0,018), although  clinically  it wasn’t significantly  different. There was  a  statistically significant  difference  in  the  level  of cholesterol  and LDL  during  the  12 month  of use Planibu® versus Depo Progestin®  (p<0,05)Conclusion: There was a  statistically significant  difference  in  the  level of  cholesterol, HDL, and SGOT    during the 12 month of use Depo Progestin®, although clinically  it wasn’t significantly different. There was a statistically significant difference in the level of  cholesterol, SGOT and SGPT during the 12 month of use Planibu®, although clinically  it wasn’t  significantly different. There was  a statistically significant difference  in  the  level of   cholesterol and LDL during  the 12 month of use Planibu® versus Depo Progestin®, although clinically  it wasn’t significantly different. There was no  difference clinically  in  the  safety  level of Planibu®  versus Depo  Progestin® shown  by measurement  result  of  liver  function and  lipid  profile  parameters.Keywords:  planibu, depo  progestin,  liver,  lipid